The developmental trajectories of racial categorization and explicit racial biases in Singapore - Lee, Kristy Jia Jin (2022)
The present study investigated the development of racial categorization and explicit racial biases in Singaporean Chinese preschoolers (N = 73). Three- to six-year-olds were found to be generally adept at categorizing novel faces by race and displayed significant improvements in their racial categorization abilities at six years old. Additionally, the strength of children's racial preferences varied along the developmental trajectory. While three- and four-year-olds did not exhibit own-race preferences, five- and six-year-olds preferred to befriend own-race children and preferentially assigned desirable jobs to own-race adults. None of the age groups, however, displayed preferences for either race when assigning undesirable jobs to adults, pointing to an absence of negative outgroup bias from three to six years old. Lastly, children who were better able to categorize novel faces by race also showed stronger tendencies to assign undesirable jobs to other-race adults and thus stronger outgroup negativity. Together, our findings suggest that ingroup positivity precedes outgroup negativity, and that racial categorization plays an important role in the development of negative outgroup bias, hence providing further support for developmental theories on intergroup bias formation.